Revealing the evolution of global energy trade patterns amidst the COVID-19 epicenter storm - Yu-Qi Liu; Shou-Xun Wen; Jun Li; Jun Yang; Xi Cheng; Chao Feng; Li-Yang Guo (Energy Strategy Reviews, 2024)
As the driving force of modern economic development, the evolution of the global energy patterns during major emergencies deserves attention. This study aims to uncover changes in global energy patterns during the COVID-19 epicenter storm. The results reveal concentrated energy trade volume in a few flows, with high-income countries holding greater influence. Amid the epicenter storm, there was a contraction in global energy trade volume, and trading patterns underwent significant shifts: (1) the global natural gas trading center shifted from the Middle East to western Africa initially, then to the United States and Russia; (2) Brazil, a crucial crude oil exporter, saw a weakened position in global crude oil exports; and (3) in the coal trading network, Australia and Russia maintained their position as trading centers throughout the storm. Swift policy adaptation is crucial for resilience and stability amid evolving global energy patterns.